EVALUATION OF THE LEVEL OF EMOTIONAL BALANCE AMONG PRINCIPALS AND TEACHERS BY EDUCATIONAL COUNSELORS (Intent Research Scientific Journal, 2025)
Feeling emotionally balanced is the basis of a person's success, creativity and innovations at work. It is represented by the feeling of emotional balance towards society. It is also considered a necessity of the product of human thought for any person in society, and at any age of his life. This always leads him to creative work and positive evaluation of the person by those around him. A person's feeling of emotional instability pushes the society around him to raise the person's awareness of himself and develop it in an ascending manner, which provides the person with a feeling of security and reassurance. However, if a person is unable to not feel balanced, this feeling increases through the fear that lies within the person's soul. A person who loses his sense of emotional stability will certainly tend to not feel secure in all aspects of his life. Problems will begin to appear, mistakes and ramifications will increase, and therefore this leads him to start thinking about destroying himself.